Filipino Muslims in Kalibo, Aklan self-concept, perceived prejudice after the 9/11 attack and their level of religiousity. - Idorot, Rena Q.
This is a descriptive study which sought to determine the following : (1) the self-concept of Filipino Muslims (2) the perceived prejudice after the 9/11 attack